2014
DOI: 10.1371/journal.pone.0093815
|View full text |Cite
|
Sign up to set email alerts
|

Model-Driven Redox Pathway Manipulation for Improved Isobutanol Production in Bacillus subtilis Complemented with Experimental Validation and Metabolic Profiling Analysis

Abstract: To rationally guide the improvement of isobutanol production, metabolic network and metabolic profiling analysis were performed to provide global and profound insights into cell metabolism of isobutanol-producing Bacillus subtilis. The metabolic flux distribution of strains with different isobutanol production capacity (BSUL03, BSUL04 and BSUL05) drops a hint of the importance of NADPH on isobutanol biosynthesis. Therefore, the redox pathways were redesigned in this study. To increase NADPH concentration, gluc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 51 publications
1
24
0
Order By: Relevance
“…Various studies have shown that several bacterial species require STH for growth under metabolic conditions with excess NADPH formation (Canonaco et al, 2001 ; Hua et al, 2003 ; Sauer et al, 2004 ; Zhao et al, 2008 ; Fuhrer and Sauer, 2009 ). Moreover, mutant bacteria suffering from a disturbed redox balance due to an increased NADPH concentration often benefit from the heterologous expression of STH (Boonstra et al, 2000 ; Angermayr et al, 2012 ; Qi et al, 2014 ; Reddy et al, 2015 ). These observations support the idea that the physiological role of STH is to convert NADPH into NADH to prevent an excess of NADPH (Voordouw et al, 1983 ), a notion that is generally accepted and is supported by actual NAD + /NADH and NADP + /NADPH ratios (see above), which indicate that the formation of NADPH from NADH will generally require energy input.…”
Section: Nadph-generating Reactions Not Coupled To Carbon Metabolismmentioning
confidence: 99%
“…Various studies have shown that several bacterial species require STH for growth under metabolic conditions with excess NADPH formation (Canonaco et al, 2001 ; Hua et al, 2003 ; Sauer et al, 2004 ; Zhao et al, 2008 ; Fuhrer and Sauer, 2009 ). Moreover, mutant bacteria suffering from a disturbed redox balance due to an increased NADPH concentration often benefit from the heterologous expression of STH (Boonstra et al, 2000 ; Angermayr et al, 2012 ; Qi et al, 2014 ; Reddy et al, 2015 ). These observations support the idea that the physiological role of STH is to convert NADPH into NADH to prevent an excess of NADPH (Voordouw et al, 1983 ), a notion that is generally accepted and is supported by actual NAD + /NADH and NADP + /NADPH ratios (see above), which indicate that the formation of NADPH from NADH will generally require energy input.…”
Section: Nadph-generating Reactions Not Coupled To Carbon Metabolismmentioning
confidence: 99%
“…Next, we repeated the electrophoretic mobility-shift assay in the presence of 10 mM ATP. We chose this concentration as representative of high physiological ATP concentration in exponentially growing B. subtilis, based on several recent studies (Kleijn et al, 2010;Qi et al, 2014). In the presence of 10 mM ATP, SalA bound efficiently to the target DNA ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Distilled water was then added to obtain a 1:1 leaf powder moisture ratio (w/v). Sealed fermentation was conducted at 30 °C for 4 days, and the Moringa proteins were then extracted …”
Section: Methodsmentioning
confidence: 99%
“…Sealed fermentation was conducted at 30 ∘ C for 4 days, and the Moringa proteins were then extracted. 25,26 Analytical methods 2 g of fermentation matter was used to determine the protein concentration of the samples at 24 h time points. With this approach, the proteins were extracted from the fermentation matter by adding approximately 10 volumes of distilled water (w/v, 20 mL) to 2 g of fermentation matter and then extracting the samples for 1 h at 60 rpm in the shaker incubator.…”
Section: Fermentationmentioning
confidence: 99%